Malassezia arunalokei sp. nov., a Novel Yeast Species Isolated from Seborrheic Dermatitis Patients and Healthy Individuals from India - Honnavar, Prasanna (J Clin Microbiol, 2016)
The majority of species within the genus Malassezia are lipophilic yeasts that colonize the skin of warm-blooded animals. Two species, Malassezia globosa and Malassezia restricta, are implicated in the causation of seborrheic dermatitis/dandruff (SD/D). During our survey of SD/D cases, we isolated several species of Malassezia and noticed vast variations within a few lipid-dependent species. Variations observed in the phenotypic characteristics (colony morphology, absence of catalase activity, growth at 37°C, and precipitation surrounding wells containing Tween 20 or Cremophor EL) suggested the possible presence of a novel species. Sequence divergence observed in the internal transcribed spacer (ITS) region, the D1/D2 domain, and the intergenic spacer 1 (IGS1) region of rDNA and the TEF1 gene, PCR-restriction fragment length polymorphism (RFLP) analysis of the ITS2 region, and fluorescent amplified fragment length polymorphism analysis support the existence of a novel species. Based on phenotypic and molecular characterization of these strains, we propose a new species, namely, M. arunalokei sp. nov., and we designate NCCPF 127130 (= MTCC 12054 = CBS 13387) as the type strain.